2017
DOI: 10.2147/dnnd.s116949
|View full text |Cite
|
Sign up to set email alerts
|

Randomized control trial evaluation of a modified Paleolithic dietary intervention in the treatment of relapsing-remitting multiple sclerosis: a pilot study

Abstract: Background/objectiveA Paleolithic diet may improve fatigue and quality of life in progressive multiple sclerosis (MS) patients, but past research has evaluated the effects of this dietary intervention in combination with other treatments such as exercise. Thus, the purpose of this pilot study was to evaluate a modified Paleolithic dietary intervention (MPDI) in the treatment of fatigue and other symptoms in relapsing-remitting MS (RRMS).MethodsWe measured the effects of a MPDI in 17 individuals with RRMS. Of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
85
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 113 publications
(97 reference statements)
3
85
2
2
Order By: Relevance
“…Due to the multimodal nature of the trial, it is not possible to determine which outcomes were specifically related to the diet. However, two small follow-up randomized controlled trials found that the study diet alone was associated with improvements in fatigue, QoL, and motor function compared to usual diet control groups [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the multimodal nature of the trial, it is not possible to determine which outcomes were specifically related to the diet. However, two small follow-up randomized controlled trials found that the study diet alone was associated with improvements in fatigue, QoL, and motor function compared to usual diet control groups [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A number of restrictive diets are promoted online and in the media for people with MS, including the Swank Diet ( 5 ) (saturated fat restricted to <20 g/day; unsaturated fat restricted to 20–40 g/day); the Overcoming MS (OMS) Recovery Program ( 6 ) (low in saturated fat; moderate in seafood, avocado and nuts; no meat, dairy, egg yolks, or refined foods); and the Paleo diet (high in meat, vegetables, and fruits; no dairy, legumes, or grains) ( 7 ). There is little empirical evidence to support the benefits of such dietary modifications for disease activity or progression in MS.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown whether the dietary component of the multimodal intervention also significantly contributed to the observed reduction in perceived fatigue [ 4 , 5 ]; however, several participants anecdotally reported that deviations from the study diet resulted in a sharp worsening of their fatigue and noted that the fatigue resolved with stricter adherence to the study diet. Data from another pilot randomized controlled trial also showed significant reductions in perceived fatigue (as assessed by FSS) in individuals with relapsing-remitting multiple sclerosis (RRMS) following a modified Paleolithic diet intervention [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The modified Paleolithic diet continues to stress a high intake of vegetables but also eliminates foods to which some individuals may be sensitive: eggs and nightshade vegetables [ 29 ]. To enhance adherence and reduce the rate of dropout, which occurred early in the intervention among participants in a nondiet control group [ 35 ], control participants will be assigned a second diet, a low saturated fat (Swank) diet, which is also popular among the MS community and has research to support its efficacy.…”
Section: Introductionmentioning
confidence: 99%